New Working Methods of Cultural Centers - Rustamov Muhammad (International Journal on Orange Technologies, 2023)
the article talks about the requirements for the management of cultural centers, the reforms implemented in the field. To provide a complete understanding of the methods of systematic organization of creative processes of cultural centers, management of the activity of clubs.